Egg retrieval in ground-nesting cuckoo hosts: can two species of buntings accurately identify and retrieve their own eggs? - Yuhan Zhang; Guo Zhong; Longwu Wang; Wei Liang (Animal Cognition)
Abstract Egg retrieval in birds may help ensure the survival of eggs and improve reproductive success. However, with the risk of brood parasitism, for ground-nesting or cavity-nesting bird hosts, there is a significant reproductive cost and thus a reduction in fitness if the host wrongly retrieved the parasitic eggs. The south rock bunting (Emberiza yunnanensis) and yellow-throated bunting (E. elegans) are hosts for common cuckoos (Cuculus canorus), which coexist within the study area and breed sympatrically in ground nests. Previous studies have found that these two species exhibit strong egg recognition and egg rejection of non-mimetic eggs. In this study, red model eggs, budgerigar eggs, and the host’s own eggs were used to assess the recognition and retrieval behavior of two bunting hosts, particularly in response to different types of eggs placed at the nest edge. The results showed that both bunting hosts retrieved ca. 80% of own eggs and did not retrieve any red model eggs. This indicated that both species could distinguish non-mimetic model eggs from their own eggs and make appropriate decisions, which is consistent with their responses when encountering foreign eggs in the nest. However, both species simultaneously retrieved some (8.3% for the yellow-throated bunting and 19% for south rock bunting) of the highly mimetic budgerigar eggs, indicating that the degree of mimicry of foreign eggs affects their egg recognition and egg retrieval behavior. Factors such as parasitism risk, nest predation pressure, age differences, and experience of parent birds may combine to influence egg retrieval behavior of the host.